Castile in the First Half of the 14th Century: a Military Revolution? (SP) (Edad Media. Revista de Historia, 2017)
In recent decades, several English and American scholars have debated over the existence of a Medieval Military Revolution. It has been argued that the main changes that characterized this phenomenon could date back to the 14th century, such as the primacy of the infantry, the emergence of military gunfire, the increasing size of armies, and the improvement in recruitment procedures. However, this debate has not paid proper attention to the Iberian kingdoms. In the fourteenth century, Castilian armies did not exhibit any substantial innovations compared to the previous century, and they still maintained several feudal features.
Keywords: military revolution; Castile; 14th Century; guerra; royal power